Rapid Identification of Dipeptidyl Peptidase-IV (DPP-IV) Inhibitory Peptides from Ruditapes philippinarum Hydrolysate - Liu, Rui (Molecules, 2017)
Dipeptidyl peptidase-IV (DPP-IV) inhibitory peptides were rapidly identified from Ruditapes philippinarum hydrolysate. The hydrolysate was fractionated by ethanol precipitation and preparative reverse phase high-performance liquid chromatography (RP-HPLC). The fraction which showed the highest DPP-IV inhibitory activity was then analyzed by a high-throughput nano-liquid chromatography electrospray ionization tandem mass spectrometry (nano-LC ESI-MS/MS) method, and the sequences of peptides were identified based on the MS/MS spectra against the Mollusca protein data from the UniProt database. In total, 50 peptides were identified. Furthermore, molecular docking was used to identify potential DPP-IV inhibitors from the identified peptides. Docking results suggested that four peptides: FAGDDAPR, LAPSTM, FAGDDAPRA, and FLMESH, could bind pockets of DPP-IV through hydrogen bonds, π-π bonds, and charge interactions. The four peptides were chemically synthesized and tested for DPP-IV inhibitory activity. The results showed that they possessed DPP-IV inhibitory activity with IC(50) values of 168.72 μM, 140.82 μM, 393.30 μM, and >500 μM, respectively. These results indicate that R. philippinarum-derived peptides may have potential as functional food ingredients for the prevention of diabetes.